2018
DOI: 10.1016/j.artd.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Superior rim fracture of a vitamin E-infused highly cross-linked polyethylene (HXLPE) liner leading to total hip arthroplasty revision

Abstract: This case report looks at the failure of a vitamin E-infused highly cross-linked polyethylene acetabular liner that fractured at the superior rim of the locking mechanism. This calls to question whether there is a problem with the vitamin E-infused product or a flaw in the design of the liner or possibly a combination of the 2. Although there has been discussion of a possible minimum rim polyethylene thickness, there has not been a minimum thickness established. In addition, in the case of offset liners, inden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…There were 2 revisions performed due to liner breakage in the VEPE group versus 3 revisions in the reference group after 2014, accounting for 5% of revisions in the VEPE group and 3% in the reference group. Reports of VEPE liner breakage in the literature are rare (Bates and Mauerhan 2015 , Brazier and Mesko 2018 ), and current data support the previous findings. Concerns over safety issues have not been raised in several previous studies, and our results are in agreement with this (Jarrett et al.…”
Section: Discussionsupporting
confidence: 90%
“…There were 2 revisions performed due to liner breakage in the VEPE group versus 3 revisions in the reference group after 2014, accounting for 5% of revisions in the VEPE group and 3% in the reference group. Reports of VEPE liner breakage in the literature are rare (Bates and Mauerhan 2015 , Brazier and Mesko 2018 ), and current data support the previous findings. Concerns over safety issues have not been raised in several previous studies, and our results are in agreement with this (Jarrett et al.…”
Section: Discussionsupporting
confidence: 90%
“…9,10,12,13,2628 To our knowledge, there has only been 2 case reports of failed VEPE explanted liners. Brazier et al 29 and Bates and Mauerhan 30 both found a cracked rim on a vitamin E liner explanted for revision within a year of surgery. They both suggest that the decreased thickness of the material, combined with introduction of larger heads could pose a risk with reference to other case reports from non-vitamin E HXLPE liners with cracked rim.…”
Section: Discussionmentioning
confidence: 99%
“…HXLPE failure and rim fractures have been reported several times due to oxidative degradation of residual free radicals, but only 2 cases of VEPE liner rim fractures have been reported to date. [ 14 , 15 ] Liner thickness, design defaults, trauma history, and improper implant position were presumed to be possible causes. However, no clear cause was found in either case, and further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%